Wykrywanie kleju żywicznego w papierowych podłożach zabytkowych fotografii oraz ich oprawach - Kozielec, Tomasz; Karbowska-Berent, Joanna (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2014)
Determination of the rosin size in ancient paper photographic supports and passe-partouts In 1807 Moritz Friedrich Illig published a new method of paper sizing. He used the rosin size for so called “internal sizing”, which was a great revolution in papermaking. This new method has been using to sizing writing, printing, artistic, and also photographic papers. It’s very important for conservators to recognize a kind of substance used for paper sizing when state of preservation is described or planned conservation wet treatments, for example. Author focused on different method of determination of the rosin size in paper samples derived from photographic supports and passe-partouts, such as: Raspail, Libermann-Storch, potassium permanganate and Herzberg reagent, Halpen-Hicks. There is an important difference in effectiveness of determination of the rosin in paper products of different quality, and having various chemical composition. Some factors, such as lignin content and remains of some substances after chemical processing of photographs limit application of some chemical tests on paper samples. Not only tests for rosin presence are important in samples investigation, but also tests with aluminon, alizarin red S, and observation of some paper properties. They are very helpful. Author discussed their possibilities and applications of use for photographic supports and passe-partouts.